Breeding Place and Resting Place Factor on DHF (Social Culture) Events In The Working Area of Pangkajene Sidrap District Maritanggae - Yunita Sari; Rahmi A.; Herlina Muin (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2020)
Dengue Hemorrhagic Fever (DHF) or Dengue Haemorrhagic Fever (DHF) which can manifest as Dengue Shock Syndrome (DSS) is an indirect infectious disease. The mode of transmission is through the vector mosquitoes Ae.aegypti and Aedes albopictus. Based on experience to date, in general the one who plays the most role in transmission is Ae.aegypti, because of his life in and around the house; whereas Aedes albopictus in gardens, so there is less contact with humans. This study aims to determine the relationship between breeding places, resting places and socio-culture with the incidence of dengue hemorrhagic fever in the working area of Pangkajene Community Health Center, Sidrap Regency.This research is a quantitative study, and uses an observational method with a cross sectional study design. Respondents in this study were 32 research instruments using questionnaires, observation sheets and interviews, analyzed using the Chi-square test.The results showed that there was no significant relationship between the breeding place and the incidence rate of dengue with p = 0.066. DHF with p value = 0.102. Outreach to the public regarding efforts to control and mitigate DHF needs to be increased as well as increased community participation through the preservation of the mosquito nest eradication program (PSN). The problem of DHF is not only a matter of the health sector, comprehensive and multisectoral countermeasures need to be done to reduce the existing risks.Keywords: Breeding Place, Resting Place, Socio-Culture, Incidence of DHF